High entropy phase evolution and fine structure of five component oxide (Mg, Co, Ni, Cu, Zn)O by citrate gel method - Sushil J.; Kumar A.; Gautam A.; Ahmad M.I. (My University, 2025)
(Mg, Co, Ni, Cu, Zn)O is an equiatomic five-component high entropy oxide (HEO), which has shown promising dielectric and intercalating properties. We report the synthesis of a phase-pure (Mg, Co, Cu, Ni, Zn)O HEO by the citrate-gel auto-combustion method and the crystallographic phase evolution as a function of annealing temperature. The powders as-synthesized by auto-combustion at 230 °C had ~85% high entropy rocksalt phase along with tenorite (CuO) and wurtzite (ZnO) phases. On annealing at the temperatures between 600 and 700 °C, the fraction of unary oxide phases ZnO, CuO, and Co3O4 (spinel) increased. On annealing at higher temperatures, the unary oxide phases dissolved, and finally, at annealing temperatures greater than 850 °C, a phase pure high entropy solid solution having rocksalt structure was obtained. All the metal ions were in +2 state, as observed from the XANES spectra. EXAFS revealed the presence of Jahn-Teller distortion in CuO6 octahedra. The structural parameters derived from EXAFS were in close agreement to that obtained from XRD measurements. © 2020 Elsevier B.V.